Reactogenicity of Cervarix and Gardasil human papillomavirus (HPV) vaccines in a randomized single blind trial in healthy UK adolescent females - Tao Haskins-Coulter; Jo Southern; Nick Andrews; Elizabeth Miller (Taylor & Francis Group, 2017)
One hundred and ninety eight females aged 12-15 y were enrolled in an observer-blinded randomized trial to assess the immunogenicity and reactogenicity of the tetravalent HPV vaccine Gardasil® (group 2), in comparison to the bivalent HPV vaccine, Cervarix® (group 1), which was routinely offered in the national vaccination schedule at the time. Participants were blinded to treatment group until all 3 vaccinations had been given, while laboratory staff were masked during testing. For the majority of local and general reactions, recipients of both vaccines reported comparable frequencies. Local and systemic events were rarely of high severity, except for tenderness at the injection site which reached a severe level after at least one of the doses in 24% of the Cervarix® group and 7% of the Gardasil® group (p = 0.001 comparing groups). For most reactions, no dose response was recorded, except for swelling with higher reporting at dose 3 (17.7%) than dose 1 (3.1%) for Cervarix®. SAE reporting was low (n = 3) and considered unrelated to either vaccine. This paper supports the body of evidence that Gardasil® has an acceptable safety profile when compared with Cervarix® and other vaccines given in the national program.